Analysis of Canola Oil in Virgin Coconut Oil Using FTIR Spectroscopy and Chemometrics - Man, Yaakob B. Che; Rohman, abdul (Journal of Food and Pharmaceutical Sciences, 2013)
Virgin coconut oil is a relative new oil comer in the industry of fats and oils, especially in ropical regions. In this study, we have investigated the possibility to use of Fourier transform infrared (FTIR) spectroscopy in combination with multivariate calibrations of partial least square (PLS) and principle component regression (PCR) as well as discriminant analysis (DA) for quantitative analysis and discrimination of canola oil (Ca-O) in virgin coconut oil (VCO). VCO, Ca-O, and the mixture of both oils was FTIR-spectroscopically scanned at mid infrared region (4,000 – 650 cm-1) using horizontal attenuated total reflectance. Several frequency regions as well as normal and derivative FTIR spectra were compared in order to obtain the best model for quantitative analysis. Finally, FTIR normal spectra at combined frequency regions of 1200-900 and 3027- 2985 cm-1 were selected for quantification of Ca-O due to their capabilities to provide the high correlation between actual and predicted values of CaO in VCO and low error values, either in calibration or validation models. Furthermore, DA was able to discriminate VCO and that adulterated with Ca-O. This result indicated that FTIR spectroscopy was possible to quantify and to discriminate Ca-O in VCO for authentication studies.Keywords: FTIR spectroscopy, canola oil, virgin coconut oil, multivariate calibration, discriminant analysis